Batuk Puter (Swabatik untuk Penguatan Karakter) - Azal, Abdul Qadimul (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2019)
At the beginning of the 2017/2018 school year, in July 2017 there were around 30% of new students (class VII) who did not wear batik clothes every Saturday. Students do not wear batik clothes because they do not have suitable batik clothes. They are considered to violate school rules. The problem that will be discussed in this best practice is how can Swabatik strengthen the student character? Swabatik is a batik activity by new students (class VII) using used clothes. Then the finished batik clothes are used as class uniforms that are worn every Saturday. The conclusion of this best practice is that swabatik can strengthen students' character, among others: (1) all students wear homemade batik clothes so that no more students violate the rules, (2) no visible gap between lucky students and less students economically lucky, (3no one of students who are inferior because they do not wear batik clothes, and (4) students learn to socialize, mutual cooperation, steadfast, patient, disciplined, organized, and creative.